Integrating the Direct Practice Approach to enhance HOTS in middle school English: Challenges and solutions - Asnawi Muslem; Sofyan A Gani; Fani Safitri; Diana Achmad; Byabazaire Yusuf (Universitas Syiah Kuala, 2026)
This study examined the effectiveness of the Direct Practice Approach (DPA) in enhancing middle school English teachers’ ability to integrate higher-order thinking skills (HOTS) into classroom instruction. Using a mixed-methods design, 50 teachers were divided equally into experimental and control groups. The experimental group received DPA-based training, while the control group continued conventional teaching methods. Data were collected through pre- and post-tests using performance-based evaluations, supplemented by in-depth interviews with 15 experimental group teachers to explore implementation challenges and strategies. The results showed significant improvement in the experimental group’s HOTS application competence, with mean scores increasing from 64.96 to 82.96, compared to modest gains in the control group. Normalized gain scores confirmed the experimental group’s superior progress. Qualitative analysis revealed recurring challenges, including insufficient training, difficulties designing HOTS-based questions, limited resources, and low student motivation. Teachers addressed these through various strategies: professional development and active learning, the use of stimuli and visual aids, policy adjustments, collaborative lesson planning, and student-centered approaches such as problem-based learning (PBL). Effective methods included visual aids, Bloom’s taxonomy-based question design, and methodical scaffolding. The findings affirm the value of DPA in bridging the gap between theory and practice in HOTS instruction, empowering teachers to apply engaging, analytical, and reflective pedagogies. The study emphasizes the importance of structured training, peer collaboration, and accessible resources in sustaining teachers’ professional growth. These results suggest that structured, practice-focused professional development effectively equips educators to promote critical thinking and analytical skills in English classrooms.